MORPHO-PHONEMIC ADAPTATION OF ENGLISH LOAN VERBS IN LUKABARAS - Sasala, James Matseshe (LLT Journal: A Journal on Language and Language Teaching, 2022)
English as an official language in Kenya has apparently influenced the Kenyan indigenous languages. Since it is the language of formal instruction in schools and other institutions, a large number of loan words have been integrated in the local languages. This paper thus investigated the adaptation of English loan verbs in Lukabaras which is one of the ethnic languages spoken in the Western region of Kenya. The study endeavoured to describe the morphological and phonological constraints evident in the integration of these items in Lukabaras. A sample of 20 lexical items was picked through purposive sampling technique and analysed descriptively. The study established that English verbs are incorporated in Lukabaras through the prefix {okhu-} and the verbal radical suffix {a}. It was further observed that in the process of integration the verbs are subject to phonological conditions such as consonant devoicing, vowel insertion, gliding and vowel reduction.